2013
DOI: 10.1364/josab.30.001794
|View full text |Cite
|
Sign up to set email alerts
|

High-order optical harmonic generation in ionization-free regime: origin of the process

Abstract: We present a new interpretation of high-order optical harmonic generation (HHG) in atomic gases interacting with laser fields. The mechanism of harmonic generation is due to the temporal evolution of the atomic electron density spatial distribution in the external laser field, and the integral energy of a high harmonic emission and an electron excitation is equal to the work executed by the laser field for an electron motion in the intra-atomic potential field. The proposed interpretation is based on the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It can be seen that the ellipticity of harmonics at θ = π/4 is higher than that at θ = π/2. Thus, the angle θ is not only control parameter for generated radiation intensity (in the wide spectral range) [24,25] but their ellipticity as well. In numerical calcul ations Δt = 0.33 fs was chosen, because it equals to half the oscillation period of the laser field at the second harmonic frequency.…”
Section: Numerical Studies Of Evolution Level Populations Effect On T...mentioning
confidence: 99%
“…It can be seen that the ellipticity of harmonics at θ = π/4 is higher than that at θ = π/2. Thus, the angle θ is not only control parameter for generated radiation intensity (in the wide spectral range) [24,25] but their ellipticity as well. In numerical calcul ations Δt = 0.33 fs was chosen, because it equals to half the oscillation period of the laser field at the second harmonic frequency.…”
Section: Numerical Studies Of Evolution Level Populations Effect On T...mentioning
confidence: 99%
“…Although some possibilities of non-resonant HHG in the intra-atomic dynamics of the electron have been theoretically predicted [9], the experiments [2][3][4] have shown that the return of the electron to the parent particle predicted by the 3-step model [10] is crucial to the existence of resonant HHG.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly admitted that mechanisms of high and low order harmonic generation are different, and especially the three steps model is typically considered to be valid only for the description of high harmonics. Different methods were used to explain the generation of the harmonics at low orders, the so-called below (and near) threshold harmonics, which photon energies are less than (comparable to) the atom ionization potential 16 17 18 19 20 21 . In most cases, the short trajectory dominates the output because its phase is less sensitive to the driving laser intensity.…”
mentioning
confidence: 99%
“…First, while the three steps model used for high orders is not directly applicable to this spectral region, it has been generalized to qualitatively understand the process 18 19 . The second way relies on the unified non-perturbative full quantum-mechanical theory of harmonic generation 21 . The theory describing both high order and below threshold harmonic generation was developed in ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation